Democracy Education in Civics Learning for Elementary Students: Pendidikan Demokrasi dalam Pembelajaran Pendidikan Kewarganegaraan bagi Siswa Sekolah Dasar - Ni Putu Krisnawati; Dewa Bagus Sanjaya; I Nengah Suastika (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Democratic education serves as a fundamental pillar in shaping the character, moral values, and civic competence required for active participation in a democratic society. Specific Background: Within the Indonesian context, Civics Education (PKn) in elementary schools acts as a strategic vehicle for internalizing these democratic principles, which are increasingly vital yet challenged by the complexities of the digital era. Knowledge Gap: Existing literature often focuses on specific learning models without comprehensively integrating democratic values, digital literacy, and digital citizenship into a unified framework for elementary-level students. Aims: This study aimed to analyze the concepts, implementation, challenges, and strengthening strategies for democratic education in primary Civics learning through a Systematic Literature Review (SLR) covering publications from 2020 to 2026. Results: The findings reveal that integrating democratic values with digital literacy, collaborative learning, and project-based approaches significantly improves students’ critical thinking, responsibility, and decision-making skills, despite ongoing constraints related to educator digital competence and facility limitations. Novelty: This study provides a comprehensive synthesis that links democratic education, digital literacy, and digital citizenship specifically for primary education, offering an integrated conceptual framework for the 21st century. Implications: Educators and policymakers are encouraged to adopt innovative, technology-integrated pedagogical practices that foster well-characterized, critical, and responsible young digital citizens. Highlights Systematic synthesis confirms that participatory and project-based learning are essential for internalizing democratic attitudes in primary education. Digital literacy and responsible technology use are critical components for modern civic engagement and character development. Teacher digital competence and infrastructure gaps remain the primary barriers to effectively implementing technology-based civic learning. Keywords Democracy Education; Civic Education; Elementary School; Digital Era; Digital Citizenship